Pengembangan potensi obyek wisata air terjun Nglirip Kabupaten Tuban - Fauzi Aziz, Khalid (Universitas Widya Mataram, 2023)
Tuban Regency is a district that has many vacationer points of interest, consisting of the Nglirip Waterfall. However, nearby travelers are much less interested by nglirip waterfall tourism due to the fact the vicinity of vacationer points of interest is pretty some distance from the middle of Tuban district. The motive of this studies is to pick out techniques in growing the tourism ability of the nglirip waterfall in Tuban Regency. The studies technique makes use of a qualitative kind with descriptive elaboration. Data evaluation strategies utilized in processing are editing, type and interpretation. The consequences of the studies information processing display that there are negative avenue conditions, negative constructing conditions, no memento kiosks, unavailable trash cans, no parking areas and no locations of worship. So tons nonetheless desires to be stepped forward to boom the splendor or promote this nglirip waterfall tour. Based at the consequences of the study, it could be defined that there may be a want to boom security, provider quality, centers on nglirip waterfall tourism with the aid of using making parking lots, trash packing containers and locations of worship. Meanwhile, to boom vacationer interest, it's far essential to innovate in virtual marketing and marketing or social media.